Implementation of moral state civil apparatus core values: a study of the influence of work culture, work discipline, and organizational commitment to the implementation of moral core values in Banyumas Regency - Titik Wahyuningsih (Universitas Wiralodra, 2023)
The launching of the Core Values and Employer Branding of the State Civil Apparatus (ASN) by the Ministry of Administrative and Bureaucratic Reform during the COVID-19 pandemic has yet to be completed. The emergence of the ASN Core Values will be a milestone in strengthening the ASN work culture. This study aims to determine the effect of work culture, work discipline, and organizational commitment on implementing core values with AKHLAK in the Government of Banyumas Regency. This study used a quantitative method in the form of a survey with a sample of 100 civil servants in the Banyumas Regency government environment. The analysis technique used to analyze primary and secondary data in this study is a linear regression analysis technique. The results are study results significant positive work culture, work discipline, and organizational commitment to the readiness of ASN in implementing core values with AKHLAK in the Government of Banyumas Regency. The results of this study imply that civil servants in the Banyumas Regency Government Environment are ready to face change and implement core values with AKHLAK.